Bronze Age Maritime and Warrior Dynamics in Island East Asia - Hudson, Mark (Social Sciences, 2022)
Recent interdisciplinary studies have provided a new perspective on the European Bronze Age. Hudson examines if these approaches can be applied to East Asia, analysing trade, maritime interactions and warrior culture in comparative Eurasian framework. This title is also available as open access on Cambridge Core.